ZnO/CuCrO2 Core–Shell Nanowire Heterostructures for Self‐Powered UV Photodetectors with Fast Response. (11th September 2018) - Cossuet, Thomas; Resende, Joao; Rapenne, Laetitia; Chaix‐Pluchery, Odette; Jiménez, Carmen; Renou, Gilles; Pearson, Andrew J.; Hoye, Robert L. Z.; Blanc‐Pelissier, Danièle; Nguyen, Ngoc Duy; Appert, Estelle; Muñoz‐Rojas, David; et al.
Abstract: An original self‐powered UV photodetector integrating ZnO/CuCrO2 core–shell nanowire heterostructures is fabricated using low‐cost and scalable chemical deposition techniques operating at moderate temperatures. A 35 nm thick delafossite phase CuCrO2 shell is formed with high uniformity by aerosol‐assisted chemical vapor deposition over an array of vertically aligned ZnO nanowires grown by chemical bath deposition. The CuCrO2 shell consists of columnar grains at the top of ZnO nanowires as well as nanograins with some preferential orientations on their vertical sidewalls. The ZnO/CuCrO2 core–shell nanowire heterostructures exhibit significant diode behavior, with a rectification ratio approaching 1.2 × 10 4 at 1 V and ‐1 V, as well as a high optical absorptance above 85% in the UV part of the electromagnetic spectrum. A high UV responsivity at zero bias under low‐power illumination of up to 3.43 mA W −1 under a 365 nm UV lamp, and up to 5.87 mA W −1 at 395 nm from spectrally resolved measurements, alongside a high selectivity with a UV‐to‐visible (395–550 nm) rejection ratio of 106 is measured. The short rise and decay times of 32 and 35 µs, respectively, both measured at zero bias, further establish these devices as promising candidates for cost‐efficient, all‐oxide self‐powered UV photodetectors. Abstract : ZnO/CuCrO2 core –shell nanowire heterostructures grown by scalable chemical deposition techniques are integrated into self‐powered UV photodetectors showing a high responsivity (5.87 mA W −1 at 395 nm) and selectivity as well as fast rise and decay times (32 and 35 µs, respectively) under zero bias. These performances establish the present heterostructures as promising candidates for cost‐efficient self‐powered UV photodetectors.